Strategi Content Marketing untuk Mendorong Engagement Pelanggan Studi Kasus: Caldera Coffee and Resto Balige - Clara Sri Putri Sitorus; Tony Rivandre Simarangkir; Mia Daniella Morette Simamora; Intan Pretti Simanjuntak; Santi Agustina Manalu (Economic Reviews Journal, 2026)
The sustainability of micro, small, and medium enterprises (MSMEs) is increasingly dependent on the efficiency of their digital processes. This study addresses the inconsistency and fluctuating sales at Caldera Coffee and Resto, a culinary business whose performance is hindered by an unstructured digital content marketing workflow. The research aimed to formulate an optimized content marketing strategy model using the rigorous framework of Business Process Improvement (BPI). Employing a qualitative descriptive approach with a case study design, the methodology focused on comparative process analysis: AS-IS (Current State) and TO-BE (Future State), complemented by correlation analysis and strategic SWOT synthesis. The AS-IS analysis successfully mapped the current ad-hoc content process and identified three critical process bottlenecks (waste): Delay in managerial approval, Rework caused by the absence of visual quality SOPs, and Context Switching leading to operational and budget inefficiency. Empirically, the study found a strong positive correlation between Customer Engagement Rate and daily sales, underscoring the necessity of quality and consistency. To eliminate these process wastes, the TO-BE model proposes a lean and standardized workflow anchored on three pillars: Content Quality Standardization (to resolve rework), Workflow De-Centralization through formalized content calendars (to eliminate delay), and Value-Based Budgeting (to ensure resource efficiency). This BPI-based model fundamentally redesigns the content creation process, offering a practical framework for the culinary sector to achieve higher content consistency, improved operational efficiency, and sustainable customer engagement.